Interrelation between payout and financing decisions: evidence from emerging markets - Pirogov, Nikita; Anilov, Artem (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Nikita Konstantinovich Pirogov - HSE. E-mail: npirogov@hse.ru Artem Eduardovich Anilov - HSE. E-mail: tema_anilov@mail.ru Financing and payout decisions generally affect company’s economic performance: they have impact (both directly and indirectly) on the free cash flow and, thus, on company’s and shareholders’ value. Search for optimal capital structure and optimal payout policy strategy that are likely to maximize shareholders’ utility resulted in the papers, dedicated to determinants of capital structure and payout policy. In such papers, one of the policies is usually treated as a determinant for another one. This bound does not let researchers to make some conclusions about existence or absence of interrelation between payout and financing choices. To capture this interrelation, simultaneous regression analysis should be performed. Researchers, though, cannot come up with unified conclusion about the existence and direction of such interrelation.The absence of certain results as well as low level of research done on emerging markets make this topic rather relevant.The results of recent research on the interrelation between payout and financing decisions are discussed in this paper. We also develop an econometric model that allows us to check the existence of interrelation in emerging markets and to compare the results to those obtained from developed markets.The article contributes to the existed literature in the following directions: first, two debt variables are taken into account (total and long-term debt) as well as two payout policy variables (total payout and dividend payout). Second, macroeconomic variables are controlled. Third, the results obtained from the companies from emerging countries are compared to those obtained from developed markets.